Navn og parallelisme - Bader, Günter (Dansk teologisk tidsskrift, 2011)
Resumé The quest for the relationship between name (the name of God as the theological focus of the Psalms) and parallelism (parallelismus membrorum as the poetical form of the Psalms) not only calls for exegetical but also for systematical explications. Having excluded (1) name without any relationship to parallelism and (2) parallelism without any relationship to name, this essay makes (3) a suggestion on the basis of Ex 3:14-15 and Roman Jakobson’s theory of the two axes of language.